Pengembangan Buku Ajar Berbasis Majalah Anak Materi Wudlu Untuk Meningkatkan Pemahaman Siswa: Development of Children's Magazine-Based Textbooks for Wudlu Materials to Improve Students' Understanding - Sugiarto, Riska; Nurdyansyah, Nurdyansah; Rais, Pandi (Halaqa: Islamic Education Journal, 2018)
The academic subject of fiqh is one of the branch in Islamic academic that used to drive muslim's students for acknowledging, understanding, and exercising the muslim's commandments. For that reason, this research take an interest on how lacking the fiqh's textbooks and how ineffective the current textbooks that available for students. The shortage of summary and exercises in many fiqh's textbooks also become another background of the problem of this research. This research has two objectives of the study: 1) to design and describe the worthiness of fiqh's textbooks on subject wudlu in form of magazines to seventh grade class MI Islamiyah Kedungpeluk, Candi, Sidoarjo. 2) to explain the significant improvement in using magazines form of textbooks fiqih on subject wudlu in seventh grade class of MI Islamiyah Kedungpeluk, Candi, Sidoarjo. This research utilize the research and development model as the research method. The research also use the same development model as Walter Dick and Lou Carey did with 9 step of learning design.The development result of teaching book fulfilled valid criteria based on the validation result of the material expert 90% the validation result of design expert 90%, the validation result of languege expert 80%, the result of individual trial 100%, the small group trial 84% and the large group 91,25%. The result of the t test using SPSS 15 significance level of 0,05 showed the statistic p-value t test was 0.00, it meant (< 0.05), that Ho was rejected and Ha was accepted. There was influences which was significance of the average score of pretest and posttest.